Hedonic or utilitarian? Exploring the impact of communication style alignment on user's perception of virtual health advisory services. Issue 2 (April 2015) - Li, Manning; Mao, Jiye
Highlights System–user communication style similarity enriches virtual advisory service user experiences. An intelligent virtual general-fitness advisor was designed and developed to empirically examine this. The more alignment with a user's Internet Slang usage patterns, the more the system leads to user engagement, transparency, enjoyment, informativeness and credibility. Hedonic aspects contribute more dominantly to user's feelings of social presence and system reuse intentions than utilitarian ones.